Exploring environmental policy adoption enablers for indoor air quality management in higher educational institutions in South Africa - Ndou, Mpho; Aigbavboa, Clinton (Frontiers in Built Environment, 2023)
TThe study seeks to investigate the extent to which the indoor air quality (IAQ) management of higher educational institutions (HEIs) in South Africa could be improved through the appropriate implementation of environmental policy adoption enablers. In the quest for improving the IAQ standards in HEIs, multiple challenges influencing its success have been documented. However, an alternative restitution to the management of IAQ is made possible through environmental behavioral change. A philosophical post-positivism stance influenced the adoption of a quantitative research approach for the study. The primary data on the views shared by various academic and administrative staff members employed by HEIs across South Africa were collected using a closed-ended questionnaire survey. A review of literature uncovered 16 influential environmental policy adoption enablers which probed the objective of the study. A four-phased data analytical approach was adopted to interpret the empirical data through performing screening and reliability assessment of the data gathered together with performing descriptive and inferential statistical evaluations to ascertain the extent of influence the surveyed policy adoption enablers have on improving the management of IAQ in HEIs. From a practical perspective, the administrative council of HEIs could consider the identified policy adoption enablers as a catalyst towards improving the pro-environmental behavior and the management of IAQ in all respective institutions. Theoretically, this study contributes to the body of knowledge as it provides factors associated with environmental policy adoptions towards IAQ management for future research in the area of environmental behavior which has been lacking in previous IAQ studies and current environmental management discourse. As an instrumental enabler, the identified policy adoption approaches could edify any existing or new institutional policy adoption initiative aimed at improving the current individual’s perception of workplace comfort, satisfaction and performance triggered directly associated with their indoor environmental conditions.